A new method for determining the absolute molarity of solutions of trypsin and chymotrypsin by using p-nitrophenyl N(2)-acetyl-N(1)-benzylcarbazate - Elmore, D. T. (1968)
1. p-Nitrophenyl N(2)-acetyl-N(1)-benzylcarbazate (NPABC) was synthesized and shown to acylate α-chymotrypsin stoicheiometrically; reaction at 25° occurs almost instantaneously at pH7·04 and within 2min. at pH5·04 and there is no observable turnover during 10min. 2. The absolute molarity of solutions of α-chymotrypsin can be determined by spectrophotometric measurement of the p-nitrophenol liberated during the acylation step; the results obtained at pH5·04 and pH7·04 agree with one another and with those determined by the method of Erlanger & Edel (1964). 3. Trypsin reacts stoicheiometrically, but more slowly than α-chymotrypsin, with NPABC, and it, like chymotrypsin, can be spectrophotometrically titrated at pH7·04. At pH5·04, however, reaction between trypsin and NPABC is sufficiently slow for the reagent to be nearly specific for α-chymotrypsin. Specificity for one or other enzyme can be ensured by using soya-bean trypsin inhibitor or the chymotrypsin inhibitor l-1-chloro-3-toluene-p-sulphonamido-4-phenylbutan-2-one. Bovine thrombin does not react with NPABC. 4. Evidence is presented that indicates that acylation of α-chymotrypsin and trypsin by NPABC occurs at the active centres of the enzymes. 5. Evidence was obtained that indicates that one or more tryptophan residues move into a more hydrophobic environment when α-chymotrypsin and trypsin are acylated by NPABC.